Desain Pengendali LQR-PID Untuk Mengendalikan Getana Pada Sistem Suspensi Seperempat Kendaraan (Quarter Car) - faizal ahmad faizal; Dian Dian Mursyitah; Ewi Ewi Ismaredah; Al Al Kautsar (UIN Sultan Syarif Kasim Riau, 2019)
Transportation is a important thing for increasing of economyc development in the world and the example a car. Car has important system that is suspension. Suspension is sustain of car and make sure comfort. Enjoy and comfort is a point riding on the street. Ideal conditions when driving is the vehicle cabin does’nt shock on bumby roads. Suspension consists of two types, passive and active. In this paper use passive because easy and conventional modeling. Passive suspension is whics is still commonly used and reduce vibration in the vehicle cabin when driving. A controller is required for maintain the comfort cabin without vibration. LQR the optimal controller to solve regulator problem. After being simulated the result is error -20.88meter and overhsoot 11.6%. PID controller is added for reduce error and overshoot. The result is error 0 meter overshoot 0% settling time 0.39, rise time 0.35 delay time 0.14. LQR-PID controller can reduce error and overshoot Keywords: LQR, LQR-PID , Suspension, Quarter Car